V·O2 responses to running speeds above VO2max - Duffield, R.; Bishop, D. (International Journal of Sports Medicine, 2008)
This study compared V·O2, heart rate (HR) and electromyographic (iEMG) responses to speeds above the velocity associated with V·O2max (v-V·O2max). Eight male, middle-distance runners performed a graded exercise test to determine V·O2max and v-V·O2max and runs to fatigue at 100 % and 110 % v-V·O2max. Breath-by-breath V·O2 and HR were continuously recorded; lactate [La-] measured pre- and post-run and iEMG measures of rectus femoris (RF) and vastus lateralis were recorded during the first and last 20 s of each run. Analysis indicated longer time to fatigue in the 100 % v-V·O2max run with no differences between conditions for V·O2 or HR amplitudes or post-run [La-] (p > 0.05). There were significantly faster tau values (p < 0.05) in the 110 % condition in V·O2 and HR. No significant correlations were observed between V·O2 or HR tau values and time to fatigue. RF iEMG was significantly larger in 110 % compared to 100 % run in the first 20 s (p < 0.05). While no association between treadmill performance and V·O2 response was evident, faster running speeds resulted in faster V·O2 and HR responses, with no difference in amplitude or % V·O2max attained. This may potentially be as a result of an increased muscle fibre recruitment stimulus during the faster running velocity resulting in faster cardiodynamic responses.